Electroacupuncture versus sham electroacupuncture in the treatment of postoperative ileus after laparoscopic surgery for colorectal cancer: study protocol for a multicentre, randomised, sham-controlled trial. Issue 4 (15th April 2022) - Zou, Xuan; Yang, Ying-Chi; Wang, Yu; Pei, Wei; Han, Jia-Gang; Lu, Yun; Zhang, Mao-Shen; Tu, Jian Feng; Lin, Lu Lu; Wang, Li-Qiong; Shi, Guangxia; Yan, Shi-Yan; et al.
Abstract : Introduction: Postoperative ileus (POI) is an inevitable complication of almost all abdominal surgeries, which results in prolonged hospitalisation and increased healthcare costs. Various treatment strategies have been developed for POI but with limited success. Electroacupuncture (EA) might be a potential therapy for POI. However, evidence from rigorous trials that evaluated the effectiveness of EA for POI is limited. Thus, the aim of this study was to examine whether EA can safely reduce the time to the first defecation after laparoscopic surgery in patients with POI. Methods and analysis: This multicentre randomised sham-controlled trial will be conducted in four hospitals in China. A total of 248 eligible participants with colorectal cancer who will undergo laparoscopic surgery will be randomly allocated to an EA group and a sham EA group in a 1:1 ratio. Treatment will be performed starting on postoperative day 1 and continued for four consecutive days, once per day. If the participant is discharged within 4 days after surgery, the treatment will cease on the day of discharge. The primary outcome will be the time to first defecation. The secondary outcome measures will include time to first flatus, tolerability of semiliquid and solid food, length of postoperative hospital stay, postoperative nausea and vomiting, abdominal distension, postoperative pain, postoperative analgesic, time to first ambulation, blinding assessment, credibility and expectancy and readmission rate. Ethics and dissemination: Ethics approval was obtained from the Ethics Committee of Beijing University of Chinese Medicine (number 2020BZHYLL0116) and the institutional review board of each hospital. The results will be disseminated through peer-reviewed publications. This study protocol (V.3.0, 6 March 2020) involves human participants and was approved by the ethics committees of Beijing University of Chinese Medicine (number 2020BZHYLL0116), Beijing Friendship Hospital Affiliated to Capital Medical University (number 2020-P2-069-01), Beijing Chao-Yang Hospital Affiliated to Capital Medical University (number 2020-3-11-2), National Cancer Center/National Clinical Research Center for Cancer/Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College (number 20/163-2359), and the Affiliated Hospital of Qingdao University (number QYFYKYLL711311920). The participants gave informed consent to participate in the study before taking part. Trial registration number: ChiCTR2000038444.